Unselected cardiac troponin testing and the diagnosis of myocardial infarction in the emergency department - Alfredo Bardají; Oscar M. Peiro; Maria Leyva-López; Juan R. Delgado; Mar Rocamora-Horach; Montserrat Galofré; Isabel Fort; Anna Carrasquer; Jose Luis Ferreiro (BMC Emergency Medicine)
Abstract Background This research examines the role of systematic cardiac troponin evaluation in identifying type 1 myocardial infarction among patients presenting to the emergency department with collected blood samples. Methods This was a prospective study of consecutive adult patients presenting to the emergency department of a university hospital between October 22, 2020, and January 11, 2021. Cardiac troponin I levels were measured in all patients, including those with suspected acute coronary syndrome (clinical testing) and a control group undergoing routine blood tests (non-clinical testing). The primary outcomes were the prevalence of type 1 myocardial infarction and the positive predictive value of cardiac troponin I, which were assessed using established statistical methods. Results Elevated cardiac troponin levels were identified in 13.4% of the study population (382/2,853). This included 19.5% of patients with clinically guided tests and 10.1% of those with non-clinical testing. The overall prevalence of type 1 myocardial infarction was 2%, with a positive predictive value of 14.9% (95% CI: 13.6–16.2). Among clinically guided tests, type 1 myocardial infarction prevalence was 5.8%, yielding a positive predictive value of 29.5% (95% CI: 26.7–32.4). Cases from non-clinically guided tests were primarily attributed to type 2 myocardial infarction or non-ischemic myocardial injury. Conclusion Using a generalized approach to cardiac troponin testing in emergency department patients significantly lowers the diagnostic accuracy for type 1 myocardial infarction, reducing the positive predictive value and frequently indicating non-ischemic myocardial injury.